Development of a Genially-Based Digital Snakes and Ladders Game to Enhance Reading Comprehension among Phase C Learners - Sari Rahayu; Lina Novita; Elly Sukmanasa (AL-ISHLAH: Jurnal Pendidikan, 2026)
Reading comprehension remains a major challenge in Indonesian elementary education, requiring innovative and engaging learning media that integrate digital technology and gamification. This study addresses the need for interactive digital learning tools by developing a Genially-based digital Snakes and Ladders game to support reading comprehension among Phase C students. This research employed a Research and Development (RD) approach using the ADDIE model. The effectiveness of the developed media was examined through a pre-experimental one-group pretest–posttest design involving 31 Phase C students. Data were collected using reading comprehension tests, expert validation sheets, and student response questionnaires. Data analysis included paired sample t-test and N-Gain to measure learning improvement. The results showed that the digital Snakes and Ladders game was feasible and appropriate based on expert validation. Students responded positively, indicating increased motivation and engagement in reading activities. Statistical analysis revealed a significant difference between pretest and posttest scores (p 0.05), with an N-Gain value of 0.71, categorized as high. This indicates a substantial improvement in students’ reading comprehension after using the Genially-based game. The findings demonstrate that integrating interactive storytelling and game-based digital media can effectively enhance reading comprehension among elementary students. The Genially-based digital Snakes and Ladders game provides an engaging learning environment that supports active participation and deeper understanding of reading texts. This media has strong potential to be adapted for other learning materials and broader educational contexts.